Development of Practical Learning Videos Based on Science, Technology, Engineering, and Mathematics (STEM) Assisted by KineMaster Application on Acid Base Material - Purba, Hengki Saputra; Afrida, Afrida; Sanova, Aulia (Indonesian Journal of Education and Mathematical Science, 2025)
This study aims to develop a STEM-based practical learning video to help students achieve learning objectives. Where in the research location, practical activities on acid-base material were not carried out due to the lack of tools and materials used in the laboratory. The development model used is the Lee Owens model, with five stages: analysis, design, implementation, and evaluation. The implementation of the research used was a teacher interview sheet, a student needs analysis questionnaire, a media expert validation questionnaire, a material expert validation questionnaire, teacher assessments and student response questionnaires. The trial was conducted on a small group of 10 students in grade XI Phase F2. The results of this development research were declared valid and suitable for use in learning. The material expert validator, the media expert validator gave a value that was suitable for testing by validating each 2 times. The teacher's assessment stated that it was suitable for testing with one validation. Students gave a good response with a value of 87.07% with the category "very suitable". Practical learning video based onscience, technology, engineering, and mathematicsThis has been proven to be valid, feasible and effective for use in acid-base learning and can help students achieve learning objectives even if they do not carry out practical activities directly in the laboratory.